Penentuan Jumlah, Titik Tengah dan Jenis dari Objek Geometri Digital dengan Metode Boundaries Menggunakan Matlab - Syafrijal Agus Mubarok; Hafizh Novanda Ichwan; Syamsudin Zubair; Yulianto (Proceedings of the Informatics Conference, 2020)
In this study, in the wake of a geometric object identification system contained in an image.Broadly speaking, this system works by reading an image contained therein image geometry.In determining an object geometry we often encounter problems either determine the type of object geometry, determines the number of geometry objects. The determination of a geometric object can help us to know the object which we will examine and may also reduce errors.Sometimes identification by conventional or manual often less precise and accurate, because this identification is done by using direct observation without the use of a digital image. With this program can be a tool for detecting an object geometry digitally and can also reduce errors at the time of detection of the object geometry.